THE SIGNIFICANCE OF QUANTITATIVE SENSORY TESTING IN PATIENTS WITH CHRONIC MUSCULOSKELETAL PAIN - Tomasevic-Todorovic, Snezana; Nikolic, Stefan; Cvetkovic, Sofija; Ilic, Natasa; Spasojevic, Tijana; Savić, Damjan (Acta medicae Medianae, 2026)
Quantitative Sensory Testing (QST) provides objective, reproducible data, which can help confirm a diagnosis or monitor treatment outcomes in patients with chronic musculoskeletal pain (CMSP). QST has the potential to become an integral part of routine clinical evaluations in a variety of chronic musculoskeletal conditions. QST can detect early sensory changes before they are clinically obvious. QST procedures are non-invasive, making them suitable for repeated assessments and monitoring over time. The standardization of testing protocols is essential for obtaining reliable results. Impaired Conditioned Pain Modulation (CPM) could serve as a biomarker for central sensitization in chronic pain conditions, helping clinicians identify patients whose pain is centrally mediated. QST has the potential to become an integral part of routine clinical evaluations in a variety of chronic musculoskeletal conditions. QST is particularly useful for evaluating the impact of physical therapies, exercise programs, and psychological interventions.